Characterization of fluoroquinolone resistance and qnr diversity in Enterobacteriaceae from municipal biosolids - Kaplan, Ella; Offek, Maya; Jurkevitch, Edouard; Cytryn, Eddie (Frontiers in Microbiology, 2013)
Municipal biosolids produced during activated sludge treatment applied in waste water treatment plants, are significant reservoirs of antibiotic resistance, since they assemble both natural and fecal microbiota, as well as residual concentrations of antibiotic compounds. This raises major concerns regarding the environmental and epidemiological consequences of using them as fertilizers for crops. The second generation fluoroquinolone ciprofloxacin is probably the most abundant antibiotic compound detected in municipal biosolids due to its widespread use and sorption properties. Although fluoroquinolone resistance was originally thought to result from mutations in bacterial gyrase and topoisomerase IV genes, it is becoming apparent that it is also attributed to plasmid-associated resistance factors, which may propagate environmental antibiotic resistance. The objective of this study was to assess the impact of the activated sludge process on fluoroquinolone resistance. The scope of resistances and mobile genetic mechanisms associated with fluoroquinolone resistance were evaluated by screening large collections of ciprofloxacin-resistant Enterobacteriaceae strains from sludge (n=112) and from raw sewage (n=89). Plasmid-mediated quinolone resistance determinants (qnrA, B and S) were readily detected in isolates from both environments, the most dominant being qnrS. Interestingly, all qnr variants were significantly more abundant in sludge isolates than in the isolates from raw sewage. Almost all of ciprofloxacin-resistant isolates were resistant to multiple antibiotic compounds. The sludge isolates were on the whole resistant to a broader range of antibiotic compounds than the raw sewage isolates; however this difference was not statistically significant. Collectively, this study indicates that the activated sludge selects for multiresistant bacterial strains, and that mobile quinolone-resistance elements may have a selective advantage in the activated sludge.